Highly enantioselective access to cannabinoid-type tricyles by organocatalytic Diels–Alder reactions - Bräse, Stefan; Volz, Nicole; Gläser, Franziska; Nieger, Martin (Beilstein Journal of Organic Chemistry, 2012)
After prosperous domino reactions towards benzopyrans, the products were used as the starting material in Lewis acid catalyzed and organocatalytic Diels–Alder reactions to build up a tricyclic system. Herein, an asymmetric induction up to 96% enantiomeric excess was obtained by the use of imidazolidinone catalysts. This approach can be utilized to construct the tricyclic system in numerous natural products, in particular the scaffold of tetrahydrocannabinol (THC) being the most representative one. Compared with other published methods, condensation with a preexisting cyclohexane moiety in the precursor is needed to gain the heterogenic tricycle systems, whereas we present a novel strategy towards cannabinoid derivatives based on a flexible modular synthesis.
Keywords: cannabinoids; Diels–Alder reaction; natural product synthesis; organocatalysis